Growth characteristics and meat quality atributes of Clam (Geloina vexans) and Oysters (Crassostrea madrasensis) harvested from two lagoons of Sri Lanka - Marapana, R. A. U. J.; Hirimuthugoda, N.Y.; Gamage, C.S; Gunarathne, S. (My University, 2014)
The present study was focused to evaluate nutritional quality parameters, Ecophysiological and commercial quality indicators of clam (Geloina vexans) and oyster (Crassostrea madrasensis) at two growth stages (4 months and 6 months) in two different Sri Lankan sites, namely Bolgoda lagoon in Moratuwa area and Pitipana lagoon in Negombo area. According to the results of this study total saturated fatty acids (34.4%) as well as total mono saturated fatty acids are high in clams of Bolgoda lagoon. However, total polyunsaturated fatty acids are high in clams of Negambo lagoon. Results revealed that crude protein level is significantly (p<0.05) higher in both species grown in Bolgoda lagoon (CP% 70.8±1.42g/100g and 48.97±2.38g/100g clams in Bolgoda and Negombo respectively while CP% 34.12+1.18 and 45.2+2.23g/100g oysters in Bolgoda and Negambo respectively). However intervalval fluid contents of 6 months age clams and oysters in Negombo are significantly higher than Bolgoda oysters (P<0.05) which are 11.39±1.68 g/100g and 9.11± 1.68 g/100g respectively. Water salinity, temperature and pH are some values which are significantly higher in Negombo lagoon than Bolgoda (P<0.05) while dissolved oxygen and resistivity are significantly higher in Bolgoda than Negombo. Results revealed that availability of planktons is high in Bolgoda lagoon. And this may be the possible reason for high CP, ash, DM and meat content in clams and oysters of Bolgoda lagoon. Rich lagoon conditions in Bolgoda lagoon has caused to the high nutritional value and high demand of bivalves in Bolgoda lagoon in Sri Lanka.
Keywords: Crassostrea madrasensis; Geloina vexans